Leading and coordinating global health: Strengthening the World Health Organization - Nirmalya Syam (South Centre, 2023)
The World Health Organization (WHO) should act as the directing and coordinating authority in global health but it has been steadily marginalized over time by design, through criticism as an inefficient organization, the reduction of assessed contributions and consequent impoverishment, and the proliferation of "new" international health agencies to which WHO has been compelled to cede operational space. This paper discusses how such marginalization of the WHO is in the interest of the dominant actors in global health, and leads to the neglect of health as a development issue. Today the global health system is more fragmented than it was when the WHO was established in 1948. Rich donor countries and corporations dominate multistakeholder governance structures in health partnerships, marginalizing most of the WHO membership and, notably, the Global South, in their decision-making. A consequence of this fragmentation in global health governance is that the space of the only multilateral organization where developing countries have an equal presence in terms of participation and decision-making as sovereign States -WHO- has been marginalized. Consequently, the development dimension of health is also marginalized and only the development assistance aspects of it receive major attention through vertical programmes and agencies addressing limited health needs without effectively addressing the basic need of strengthening health systems. Therefore, for developing countries it is imperative that WHO is effectively retooled to act as the leading and coordinating authority on global health with adequate legal powers, as well as institutional and financial capacities to do so without undue influence from donor countries and entities that have interests in the private sector. This would enable WHO to ensure that the interests of all countries are fairly addressed in its normative and operational activities. Such a transformation of WHO would require action both within and outside the organization. The paper proposes some suggestions in this regard.
Keywords: 300; Access to Medicines; COVID-19; Epidemics; Essential Drugs; Food Standards; Global Health; Health; Health Security; Health Systems; Intellectual Property; International Cooperation; Pandemic; Primary Health Care (PHC); World Health Organization (WHO)